Jilidan Journal of Pediatric Nursing: Nursing Care of Children and Families Vol.29 Issue 1, 2, 3, 4, 5, 6 Januari-Desember 2014 Editor, Cecily Lynn Betz - Redaksi (Elsevier, 2014)
JURNAL KEPERAWATAN ANAK